Patterns of economically safe restructuring of Russian industry - I. V. Matskulyak; N. V. Sanin (Вестник университета)
The purpose of the article is to propose the main patterns of restructuring (structural changes) of the Russian industrial economy. The task of the study is to reveal the essence and substantiation of each of the formulated patterns. The subject of the publication is the organizational and economic relations arising during the safe restructuring of the Russian industry. The methodology of the study proceeds from objectively existing, recurring, significant dynamic, static or combined relationships and dependencies of phenomena and processes of social production, which characterize the increase in the aggregate result of the country’s industrial system functioning. The main results are reduced to the definition of nine patterns of economically safe restructuring with the justification of each of them and the specification of their essence. Their scientific understanding is quite applicable both in educational institutions of the country in the study of economic theory and security, the restructuring of the industrial economy, and the economic practice of structural changes at all government levels. A general conclusion has been formed, expressing the content of the main patterns of safe industrial restructuring as an economic concept and its objective foundations.